2021
DOI: 10.1021/acsami.1c07178
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Ionic Porous Organic Polymers Exhibiting High Iodine Uptake from Both the Vapor and Aqueous Medium

Abstract: Large-scale generation of radioactive iodine (129I, 131I) in nuclear power plants pose a critical threat in the event of fallout, thus rendering the development of iodine sequestering materials (from both the vapor and aqueous medium) highly pivotal. Herein, we report two chemically stable ionic polymers containing multiple binding sites, including phenyl rings, imidazolium cations, and bromide anions, which in synergy promote adsorption of iodine/triiodide anions. In brief, exceptional iodine uptake (from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 52 publications
0
46
0
Order By: Relevance
“…[13a,c, 14] In principle,C OFs can be functionalized with the desired adsorption active sites (e.g., ionic sites) through the design of appropriate monomers or post-synthesis modification to achieve high I 2 adsorption capacity. [15] However,i n practice,i ti sv ery challenging to incorporate ionic sites into COFs while maintaining high crystallinity and porosity.T he "multivariate" strategy,b ased on the use of two or more structurally homologous monomers to simultaneously incorporate multiple groups into the COF structure,p rovides additional flexibility for functionality engineering. [14a, 16] The few successful examples of ionic COFs were synthesized using the "multivariate" strategy combined with subsequent surface reactions;h owever, these COFs were not tested for I 2 capture.…”
Section: Introductionmentioning
confidence: 99%
“…[13a,c, 14] In principle,C OFs can be functionalized with the desired adsorption active sites (e.g., ionic sites) through the design of appropriate monomers or post-synthesis modification to achieve high I 2 adsorption capacity. [15] However,i n practice,i ti sv ery challenging to incorporate ionic sites into COFs while maintaining high crystallinity and porosity.T he "multivariate" strategy,b ased on the use of two or more structurally homologous monomers to simultaneously incorporate multiple groups into the COF structure,p rovides additional flexibility for functionality engineering. [14a, 16] The few successful examples of ionic COFs were synthesized using the "multivariate" strategy combined with subsequent surface reactions;h owever, these COFs were not tested for I 2 capture.…”
Section: Introductionmentioning
confidence: 99%
“…14,38,39 Rarely a material is reported that demonstrated iodine adsorption in all different media which include vapor phase, organic phase and aqueous phase. 40 Besides that in most cases, the iodine adsorption ability in the organic phase and water is lower and demands improvement.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Thec rystallinity of COFs provides aw elldefined porosity and full accessibility to active sites in the framework, which are beneficial for many applications in [*] Dr.Y .Xie, Dr.T .Pan, Dr.Q.Lei, Dr.C.Chen, Dr.X.Dong, Dr.J.Shen, Prof. Dr. [13a,c, 14] In principle,C OFs can be functionalized with the desired adsorption active sites (e.g., ionic sites) through the design of appropriate monomers or post-synthesis modification to achieve high I 2 adsorption capacity. [15] However,i n practice,i ti sv ery challenging to incorporate ionic sites into COFs while maintaining high crystallinity and porosity.T he "multivariate" strategy,b ased on the use of two or more structurally homologous monomers to simultaneously incorporate multiple groups into the COF structure,p rovides additional flexibility for functionality engineering. [14a, 16] The few successful examples of ionic COFs were synthesized using the "multivariate" strategy combined with subsequent surface reactions;h owever, these COFs were not tested for I 2 capture.…”
Section: Introductionmentioning
confidence: 99%